Informed capital in a hostile environment: the case of relational investors in Germany - Dorothea Schäfer; Dirk Schilder (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
Informed capital is a crucial ingredient to a well-functioning market for start-up finance, especially in times of difficult market conditions. For bank-based systems, the question regarding which investors actually supply informed capital has not yet been answered. To fill this gap, we conduct a survey among 85 German suppliers of start-up finance. We find significant differences between the investors which are linked to banks and those financiers which are not. Although, the bank-related group, including public equity suppliers, delivers some sort of informed capital, venture capital companies and Business Angels are the key providers of informed capital in the German market for start-up finance.
Keywords: G21; G24; D21; M13; O16; 330; Informed capital; start-up financing; venture capital; banks